(untitled) (Bangladesh Journal of Otorhinolaryngology, 2016)
The study was conducted to detect and analyze the different types of ossicular chain defect in chronic suppurative otitis media with cholesteatoma on mastoid exploration and to identify the ossicle most commonly eroded by the disease process. A total 60 cases of CSOM with cholesteatoma of different age groups, who underwent surgery were included in this study and their intra operative ossicular chain findings were noted. 100% cases were presented with long standing aural discharge. It was observed that cholesteatoma was more common in male (60%) than female (40%) and 53.33% patients were in young age group (21-35 years). 90% cases showed ossicular erosion while only 10% cases showed intact ossicles. The incus was found to be absent in 15% cases and eroded in 75% cases. And the malleus was observed as the most resistant ossicle to be eroded. Bangladesh J Otorhinolaryngol; October 2015; 21(2): 97-101